2017
DOI: 10.1007/s10857-017-9380-4
|View full text |Cite
|
Sign up to set email alerts
|

Video as a tool for focusing teacher self-reflection: supporting and provoking teacher learning

Abstract: Understanding teacher knowledge and expertise is crucial to the promotion of teacher learning and the appropriate focus of any analysis aimed at understanding the development of teacher knowledge and expertise is natural classroom practice. Video provides a unique opportunity to capture some of the complexity of this practice in situ, opening up possibilities for its observation and analysis. This paper describes the research landscape related to the use of video for promoting teacher learning, drawing on a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 13 publications
2
33
0
4
Order By: Relevance
“…(2016) provided an example of video analysis that examined students' emotional engagement in history learning. In another similar study, Hollingsworth and Clarke (2017) reported that videos have been regarded as a catalyst for teachers’ professional learning ( Hollingsworth and Clarke, 2017 ). Visual data are ideal for studying situational dynamics as compared to retrospective interviews and surveys which are not powerful enough to capture or record details about situation ( Nassauer and Legewie, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2016) provided an example of video analysis that examined students' emotional engagement in history learning. In another similar study, Hollingsworth and Clarke (2017) reported that videos have been regarded as a catalyst for teachers’ professional learning ( Hollingsworth and Clarke, 2017 ). Visual data are ideal for studying situational dynamics as compared to retrospective interviews and surveys which are not powerful enough to capture or record details about situation ( Nassauer and Legewie, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, teachers can be encouraged to reflect on their existing beliefs and personal histories concerning rigor of instruction for ELs by responding, either verbally or in writing, to specially crafted questions or assignments. Some teacher educators advocate interview processes and/or class discussions to induce reflection (e.g., Hollingsworth & Clarke, 2017; Moyer & Milewicz, 2002). Others ask novice and veteran teachers to write journal entries or response papers (sometimes in response to specific questions and sometimes in an unrestricted format) or compile a portfolio (Bain et al, 2002).…”
Section: Adding Linguistic Support To Maintain Academic Rigormentioning
confidence: 99%
“…Analysis provides varied learning opportunities and in addition enables colleagues to learn about their skills and those of others (Chan et al., 2017). Mentoring through analysis of videos describing interactions occurring in the organization, helps mentees to sharpen their world-view and professional vision, leading to testing strategies for solution (Hollingsworth & Clarke, 2017).…”
Section: Introductionmentioning
confidence: 99%